IMPLEMENTASI METODE MONTESSORI SEBAGAI WUJUD PENDIDIKAN BERPUSAT PADA ANAK DI TK TUNAS BANGSA - Finnas, Fara Fauza; Minarti, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Montessori method as a form of child-centered education at TK Tunas Bangsa. The research employs a qualitative approach using a field study method. Data were collected through observations, interviews with the principal, teachers, and parents, as well as documentation of learning activities. The results show that the application of a child-centered education paradigm at TK Tunas Bangsa is reflected in learning activities that provide children with opportunities to explore, choose their learning activities, and actively engage in the learning process. Teachers act as facilitators who guide and create a pleasant learning environment in accordance with the children’s developmental stages. In addition, the implementation of this method is also evident in the application of the Merdeka Belajar concept, responsive classroom management, efforts to ensure equitable access to education, and educational transformation through the use of innovative learning media. Overall, the application of a child-centered education paradigm contributes positively to creating active and inclusive learning while supporting children’s holistic development as part of efforts to realize high-quality future education.